2012
DOI: 10.1128/aem.06792-11
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptomic and Proteomic Responses of Dehalococcoides ethenogenes Strain 195 to Fixed Nitrogen Limitation

Abstract: Bacteria of the genus Dehalococcoides play an important role in the reductive dechlorination of chlorinated ethenes. A systemslevel approach was taken in this study to examine the global transcriptomic and proteomic responses of exponentially growing cells of Dehalococcoides ethenogenes strain 195 to fixed nitrogen limitation (FNL), as dechlorination activity and cell yield both decrease during FNL. As expected, the nitrogen-fixing (nif) genes were differentially upregulated in the transcriptome and proteome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 58 publications
(83 reference statements)
1
29
0
Order By: Relevance
“…A previous microarray study also displayed a tight correlation (R 2 = 0.997) between the S-layer and tceA transcripts in a batch culture study of D2 [13]. This conserved relationship is notable because the S-Layer and major RDase proteins are among the most abundant proteins detected in proteomic assays for Dhc samples across cultures [17, 3638]. As the major components of the cell wall and membrane-associated respiration processes, the expression of these transcripts may be tightly linked in both cultures because of their requirement for biomass growth.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…A previous microarray study also displayed a tight correlation (R 2 = 0.997) between the S-layer and tceA transcripts in a batch culture study of D2 [13]. This conserved relationship is notable because the S-Layer and major RDase proteins are among the most abundant proteins detected in proteomic assays for Dhc samples across cultures [17, 3638]. As the major components of the cell wall and membrane-associated respiration processes, the expression of these transcripts may be tightly linked in both cultures because of their requirement for biomass growth.…”
Section: Resultsmentioning
confidence: 92%
“…Previous investigations have utilized various techniques, such as differential expression analyses and gene clustering, to relate transcript abundance to an experimental condition and to predict the function of the enzymes encoded on the expressed transcripts in Dhc . These studies include investigations of Dhc as the organism transitions from exponential growth to stationary phase [13], biosynthesizes molecules through the central carbon metabolism pathway [14], acquires and modifies key cobalamin cofactors required for growth [15], fixes nitrogen [16], or grows under nitrogen limitation [17]. These transcriptomic and proteomic studies have shown success in producing, testing, and supporting hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…This genus, although phylogenetically distant to Dehalobacter, inhabits similar ecological niches, and is exclusively dependent on OHR metabolism with H 2 as electron donor. These studies have used both transcriptomics using full genome microarrays and proteomics to identify key components of the metabolism of OHRB under different growth conditions or growth phases [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Many such studies in Dehalococcoides have been conducted recently. These include studies focused on: regulation of functional genes and cell cycle genes [47,48], fixed nitrogen limitation [60,61], chemical stressors such as acid and oxygen [56], corrinoid limitation [62], coculture growth with Desulfovibrio and Methanobacterium [63], exogenous amino acid provision [64], carbon metabolism [65], and elucidation of a novel citrate synthase [66 ]. Outside the Dehalococcoides, two studies have characterized genome-wide expression patterns as a function of electron acceptors and donors provided: one in Desulfitobacterium strain Y51 [67] and the other in Desulfitobacterium strain TCE1 [68].…”
Section: Genome-informed Studiesmentioning
confidence: 99%